Pretoria Student Law Review 2017-11 (Pretoria University Law Press (PULP), 2017)
It is with great joy that I, along with the editorial committee, present to you, reader, the 2017 Pretoria Student Law Review. On this journal's 11th edition, it has been an expansive year with a wider variety of topics being researched and produced by our authors. As law students, young scholars and future legal practitioners, we have a duty to utilise the unique position that we are in to challenge the status quo. Fittingly, the topics covered prove themselves to be contemporary and legally pertinent and encourage critical thinking of the law and its place in South African society. This year has not only been a challenging one for students, staff and parents but also for the citizens of South Africa as a whole. It is thus with even greater pleasure that we offer our humble contribution to legal academia. Every year of publication faces its own challenges, and this year was no different. However, it is through setbacks and ambitious deadlines that which makes a finalised product that much more deserved. This year's edition touches on a variety of themes which is certain to pique anyone's interest. This year's edition of the PSLR would not have been possible without the dedication and hard work of a particularly motivated and dedicated team. To Simon Botha, Privilege Chanana, Rutendo Chinomona, Roxanne Gilbert, Lethabo Mailula, Agnes Matasane, Raeesah Thomas, Thomas White and Jurgen Zwecker for your long hours and persistence in the production of this year's edition. You all have contributed to the mechanism of this wonderful team and it has been a privilege to have worked with you. I would further like to thank the authors for their submissions and tireless efforts to produce quality articles. My further thanks to Prof Andre Boraine and Lizette Hermann for their consistent guidance and leadership this year. This year's edition would not be the success it is without their encouragement and input this year. A further thank you to Prof Philip Stevens for his contributions and input. I would also like to thank Adebayo Okeowo for his contribution for the cover for this year's edition. I trust you, the reader, will find the included articles as insightful and though-provoking as the editorial team did. Sarah Burford Managing editor